Energy-Efficient GHz-Class Charge-Recovery Logic. - Sathe, V. S.
In this paper, we present Boost Logic, a charge- recovery circuit family that can operate efficiently at clock frequencies in excess of 1 GHz. To achieve high energy efficiency, Boost Logic relies on a combination of aggressive voltage scaling, gate overdrive, and charge-recovery techniques. In post-layout simulations of 16-bit multipliers with a 0.13-mum CMOS process at 1GHz, a Boost Logic implementation achieves 5 times higher energy efficiency than its minimum-energy pipelined, voltage-scaled, static CMOS counterpart at the expense of 3 times longer latency. In a fully integrated test chip implemented using a 0.13-mum bulk silicon process and on-chip inductors, chains of Boost Logic gates operate at clock frequencies up to 1.3 GHz with a 1.5-V supply. When resonating at 850 MHz with a 1.2-V supply, the Boost Logic test chip achieves 60% charge-recovery
Keywords: 0.13 micron; 1 GHz; 1.2 V; 1.5 V; 850 MHz; CMOS process; Boost logic gates; Bulk silicon process; Charge-recovery techniques; Gate overdrive; Multipliers; On-chip inductors; Voltage scaling